2007
DOI: 10.1161/atvbaha.106.138602
|View full text |Cite
|
Sign up to set email alerts
|

CYP26 Inhibitor R115866 Increases Retinoid Signaling in Intimal Smooth Muscle Cells

Abstract: Objective-Intimal smooth muscle cells (SMCs) are dedifferentiated SMCs that have a powerful ability to proliferate and migrate. This cell-type is responsible for the development of intimal hyperplasia after vascular angioplasty. Retinoids, especially all-trans retinoid acid, are known to regulate many processes activated at sites of vascular injury, including modulation of SMC phenotype and inhibition of SMC proliferation. Intracellular levels of active retinoids are under firm control. A key enzyme is the all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…Therefore, our results showing that inhibition of CYP26 and more specifically, CYP26B1, increases retinoid signaling in human vascular cells adds new insight into the role of CYP26 in vascular cells and suggests a potential novel way to circumvent the development of retinoid resistance. The effects of R115866 on retinoid catabolism in AOSMCs demonstrated in this study are in agreement with our previous study in rat-derived intimal SMCs [27]. Interestingly, whereas retinoid levels in rat intimal SMCs were declining 24 h after R115866 stimuli [27], this decrease in cellular retinoic acid levels was not observed in AOSMCs.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Therefore, our results showing that inhibition of CYP26 and more specifically, CYP26B1, increases retinoid signaling in human vascular cells adds new insight into the role of CYP26 in vascular cells and suggests a potential novel way to circumvent the development of retinoid resistance. The effects of R115866 on retinoid catabolism in AOSMCs demonstrated in this study are in agreement with our previous study in rat-derived intimal SMCs [27]. Interestingly, whereas retinoid levels in rat intimal SMCs were declining 24 h after R115866 stimuli [27], this decrease in cellular retinoic acid levels was not observed in AOSMCs.…”
Section: Discussionsupporting
confidence: 93%
“…The effects of R115866 on retinoid catabolism in AOSMCs demonstrated in this study are in agreement with our previous study in rat-derived intimal SMCs [27]. Interestingly, whereas retinoid levels in rat intimal SMCs were declining 24 h after R115866 stimuli [27], this decrease in cellular retinoic acid levels was not observed in AOSMCs. The increased retinoic acid degradation in rat intimal SMCs may reflect a stronger and faster CYP26 induction in these cells compared to human AOSMCs.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We and others previously showed that pharmacological inhibition of CYP26, or RNA interference (RNAi)-mediated CYP26 silencing, increases levels of retinoic acid and retinoid signaling (27,28,42). Hence, because our data indicate that the CYP26B1 enzyme was present and upregulated in atherosclerosis, regulation of CYP26B1 activity may influence atherosclerosis development by altering the local availability of retinoid ligands.…”
Section: Discussionmentioning
confidence: 99%
“…CYP26B1 has 41% amino acid identity with CYP26A1 but similar functional activity (24,25). In subsets of vascular and immune cells, interference with CYP26 has profound effects on atRA levels (26)(27)(28), and increased levels of endogenous atRA result in induction of a number of retinoid-responsive genes in vascular cells (27). To date, little is known about the significance of genetic polymorphisms that occur in the CYP26 enzymes.…”
Section: Introductionmentioning
confidence: 99%